(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the importance of communication with parents and psychopedagogical cooperation in the process of working with children in need of speech therapy. Active participation of parents in speech therapy of children with speech development delays is an important factor in strengthening exercises, emotional support, motivation and creating an environment. The study examines family upbringing methods, speech therapist-parent triad communication and methods of counseling. Attention is also paid to simple and effective types of exercises that can be performed at home. This article is based on modern approaches at the intersection of special pedagogy, speech therapy and family psychology and includes methodological recommendations for practicing specialists.